2006
DOI: 10.1002/anie.200602925
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Ene Reaction of Cyclopentadiene and α,β‐Enals Catalyzed by a Diphenylprolinol Silyl Ether

Abstract: The opposite result: A diphenylprolinol silyl ether promotes an intermolecular enantioselective ene reaction of α,β‐enals with cyclopentadiene. This is the first example of cyclopentadiene acting as the ene component, and not the diene, with α,β‐enals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
44
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 123 publications
(45 citation statements)
references
References 49 publications
0
44
0
1
Order By: Relevance
“…A reaction did not occur in the presence of either proline or trifluoromethyl-substituted diarylprolinol 4 (Figure 1), which afforded good results in the Mannich reaction [5] and the aldol reaction [4] of acetaldehyde, respectively. Although diphenylprolinol 2 did not promote the reaction, silyl ether 1, which was developed by our group, [8,10] was effective and provided the Michael product in good yield with excellent enantioselectivity. Notably, the reactivity of diphenylprolinol silyl ether 1 [11] and that of trifluoromethylsubstituted diarylprolinol silyl ether 3, [11] which is an effective organocatalyst in several asymmetric reactions developed by Jørgensen and co-workers, [12] are very different in the present reaction.…”
mentioning
confidence: 95%
“…A reaction did not occur in the presence of either proline or trifluoromethyl-substituted diarylprolinol 4 (Figure 1), which afforded good results in the Mannich reaction [5] and the aldol reaction [4] of acetaldehyde, respectively. Although diphenylprolinol 2 did not promote the reaction, silyl ether 1, which was developed by our group, [8,10] was effective and provided the Michael product in good yield with excellent enantioselectivity. Notably, the reactivity of diphenylprolinol silyl ether 1 [11] and that of trifluoromethylsubstituted diarylprolinol silyl ether 3, [11] which is an effective organocatalyst in several asymmetric reactions developed by Jørgensen and co-workers, [12] are very different in the present reaction.…”
mentioning
confidence: 95%
“…Barbas and co-workers reported that prolinol is an effective organocatalyst in an enantioselective fluoroaldol reaction, in which a similar transition state was proposed. [17] Though the electrophile attacks from the side opposite to the bulky diphenylmethyl moiety in the reaction catalyzed by a diphenylprolinol silyl ether, [11] the aldehyde reacts on the more hindered face of the catalyst in the present case. This is because the aldehyde is activated by coordination to the proton of the hydroxy group through a hydrogen bond.…”
mentioning
confidence: 96%
“…In particular, the trialkylsilyl-protected diarylprolinols (4-6) pioneered by Hayashi and coworkers and Jørgensen and co-workers provided the product in excellent chemical yield and with high enantioselectivity. [6] With respect to our hypothesis concerning the pK a window accessible for catalysis with these catalysts, the analogous phenylthioester of 1 a was unreactive, whereas the trifluoroethyl thioester was reactive.…”
mentioning
confidence: 96%
“…[3,6] As illustrated in Scheme 2, we screened a number of these organocatalysts together with benzoic acid co-catalyst, for catalysis of the Michael addition of thioester 1 a to cinnamaldehyde 2 a. A number of the pyrrolidine-based catalysts were effective.…”
mentioning
confidence: 99%